2007
DOI: 10.1007/s10750-007-9255-2
|View full text |Cite
|
Sign up to set email alerts
|

Models of stream habitat characteristics associated with tubificid populations in an intermountain watershed

Abstract: Habitat assessments were conducted in an intermountain watershed at three spatial extents to explore ways to predict the presence of tubificid oligochaetes likely to support the parasite Myxobolus cerebralis, cause of salmonid whirling disease. Stream reaches with six different reach slope characteristics were selected using GIS. The aquatic habitat in 60 reaches selected at random was measured and classified into distinct habitat units. Within the habitat units, areas of microhabitat with depositional fine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Infection rates ranged from 0% to 100% in the tributaries occupied by mountain whitefish as well as a pattern of high TAM exposure (67-76% of group scores ≥ grade 3) throughout the main stem of the Blackfoot River. This variation among streams conforms to a basin-scale pattern of increasing infection in the downstream direction (Pierce et al 2009), as broadly observed across the Intermountain West (Sandell et al 2001;de la Hoz Franco and Budy 2004;Anlauf and Moffitt 2008). In our study area, the low-elevation presence of M. cerebralis largely overlaps with the distribution of mountain whitefish with the exception of the Clearwater River, which flows through a series of glacially formed lakes as well as cold, rocky, basin-fed, forested streams with low levels of fine instream sediment, such as Gold Creek and the North Fork Blackfoot River.…”
Section: Parasite Distribution and The Influence Of Groundwatersupporting
confidence: 73%
“…Infection rates ranged from 0% to 100% in the tributaries occupied by mountain whitefish as well as a pattern of high TAM exposure (67-76% of group scores ≥ grade 3) throughout the main stem of the Blackfoot River. This variation among streams conforms to a basin-scale pattern of increasing infection in the downstream direction (Pierce et al 2009), as broadly observed across the Intermountain West (Sandell et al 2001;de la Hoz Franco and Budy 2004;Anlauf and Moffitt 2008). In our study area, the low-elevation presence of M. cerebralis largely overlaps with the distribution of mountain whitefish with the exception of the Clearwater River, which flows through a series of glacially formed lakes as well as cold, rocky, basin-fed, forested streams with low levels of fine instream sediment, such as Gold Creek and the North Fork Blackfoot River.…”
Section: Parasite Distribution and The Influence Of Groundwatersupporting
confidence: 73%
“…S1A, available online). Previous studies have demonstrated that species of Tubificidae prefer living in silt-clay and fine sand sediments (Anlauf and Moffitt, 2008) and selectively feed on finer particles less than 63 mm in diameter (Rodriguez et al, 2001;Anlauf and Moffitt, 2008). In contrast, fine sediment can significantly reduce the survivorship of gastropods and bivalves by limiting their feeding behaviors (Donohue and Irvine, 2003;Schmidlin and Baur, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fine sediment and suspended particles can significantly reduce the survival of unionids by restricting their feeding behaviors (Donohue and Irvine, 2003). In contrast, species of Annelida prefer living in mud and fine sand sediments and selectively feed on finer organic particles (Anlauf and Moffitt, 2008). Substrate stability is important for mussel habitats, and a positive relationship between substrate stability and mussel abundance has been observed in several studies (Allen and Vaughn, 2010;Johnson and Brown, 2000).…”
Section: > Decadal Changes and Implications For Conservationmentioning
confidence: 99%